Constituent Quark Scaling of Strangeness Enhancement in Heavy-Ion Collisions - Nirbhay K. Behera; Raghunath Sahoo; Basanta K. Nandi (Advances in High Energy Physics)
In the framework of a nuclear overlap model, we estimate the number of nucleons and quark participants in proton-proton, proton-nucleus, and nucleus-nucleus collisions. We observe the number of nucleon- (